ENHANCING SOCIAL-EMOTIONAL LEARNING THROUGH STORYTELLING STRATEGIES FOR BULLYING PREVENTION IN PRIMARY EDUCATION - Sindi Aulya; Umar; Abdul Haris (Universitas Islam Negeri Mataram, 2026)
This study investigates the challenges of maintaining learning focus among a student with special needs in an elementary school in Karawang. Difficulties in sustaining attention were found to significantly affect classroom participation and academic outcomes, underscoring the need for appropriate educational support, particularly through the involvement of a shadow teacher. This research adopts a qualitative descriptive approach. Data were collected through classroom observations, interviews with tahfidz teachers and shadow teachers, and document analysis. The findings indicate that: (1) students’ difficulties in maintaining focus are influenced by individual characteristics, the learning environment, and instructional practices; and (2) shadow teachers employ various strategies, including individualized assistance, adaptive instruction, emotional support, and structured guidance, to enhance students’ focus and engagement. In conclusion, shadow teachers play a pivotal role in supporting students with special needs, particularly in improving attention and active participation within inclusive classroom settings.